Mark Felt [videorecording (DVD)] : the man who brought down the White House - Landesman, Peter, 1965-; Neeson, Liam; Lane, Diane; Csokas, Marton, 1966-; Hall, Michael C., 1971-; Felt, W. Mark, 1913-2008 (Sony Pictures Home Entertainment, 2018)
The story of Mark Felt, who under the name Deep Throat helped journalists Bob Woodward and Carl Bernstein uncover the Watergate scandal in 1972.